Appropriate treadmill exercise improves survival after gut ischemia reperfusion in mice. (June 2019) - Higashizono, Kazuya; Fukatsu, Kazuhiko; Watkins, Ayako; Watanabe, Tomoki; Noguchi, Midori; Murakoshi, Satoshi; Yasuhara, Hiroshi; Seto, Yasuyuki
Summary: Background＆aims: It is unclear whether or not an appropriate prehabilitation protocol ameliorates surgical stress, ultimately improves survival after severe surgical insults. Methods: Male C57BL/6J mice received treadmill exercise according to the following protocols.Exp.1) Sixty-min treadmill running at 20 m/min. The exercise sessions were 5 days/week for 2 weeks, 3 days/week for 2 weeks or 3 days/week for 3 weeks (n = 29). Sedentary mice (n = 6) did not perform treadmill exercise. After finishing each protocol, the exercise completion rate was evaluated. All mice which had completed the protocol (n = 24) underwent 45 min superior mesenteric artery occlusion and reperfusion (Gut I/R) and survival after gut I/R was observed.Exp.2) According to the results of Exp.1, the exercise frequency and duration were set at 3 days/week for 3 weeks. To determine the appropriate running speed, mice (n = 94) ran on the treadmill for 60 min at 12, 15 or 18 m/min, while sedentary mice (n = 25) did not. The exercise completion rate and survival were observed. Results: Exp.1) The 3 days/week for 3 weeks exercise protocol showed the highest survival rate. However, the completion rate of each exercise group was only 50–60%.Exp.2) The completion rates at 15 m/min and 18 m/min were both approximately 90%. None of the 12 m/min group failed to complete the protocol. The 12 m/min and 15 m/min treadmill running groups showed equally improved survival as compared to the sedentary group (p < 0.05). Conclusions: An appropriate exercise protocol improves survival after gut I/R in mice. Prehabilitation strengthens resistance to severe surgical insults.